Implementation of green communication in the city of Surabaya to build a clean and sustainable environment - Akhmad Yusuf ZUHDY; Totok SOEHARTANTO; Ifarrel Rachmanda HARIYANTO (Smart Cities and Regional Development Journal)
The city of Surabaya in the East Java region, as the second largest city in Indonesia, has a population of around 4 million people in 2023, is one of the cleanest cities in Indonesia and even won the ASEAN Environmentally Sustainable City (ESC) award in the Cleanest Big City Air category according to the criteria clean air, clean land, and clean water. In achieving this achievement, the Surabaya city government has provided education to the people of the city of Surabaya to behave in a way that cares for a healthier and more sustainable environment, including through the arrangement of green open spaces which reached 21.99% (exceeding the Indonesian national performance index of 20%) or an area of ​​7,357.96 hectares (ha) of the Surabaya city area of ​​33,451 ha, this green space is capable of absorbing 642,794.59 tonnes/year of CO2 gas. Apart from that, the Surabaya government also carries out emission tests in different places on non-electric motorized vehicles 4 times a month in different places and urges the public to use comfortable public transportation in the form of Suroboyo buses for routes in the city and Wira Wiri micro buses for routes through village. So it has an impact on the quality of the city of Surabaya with an AQI (Air Quality Index) index of 90.31 (medium). Apart from that, the city of Surabaya has a website that displays the air quality in the city of Surabaya in real-time, which is equipped with instructions for Surabaya residents to use personal protective equipment and avoid areas with poor air quality.